2018
DOI: 10.1016/j.ecoenv.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Are the damaging effects induced by the imazethapyr formulation Pivot® H in Boana pulchella (Anura) reversible upon ceasing exposure?

Abstract: In the present study, the damage recovery capabilities of Boana pulchella tadpoles after acute exposure (96h) to 0.39mg/L concentration of the imazethapyr (IMZT)-based herbicide formulation Pivot H (25% IMZT LC value) were assessed during a period of 7 to -21 days. To appraise the recovery capabilities, frequency of micronuclei (MNs), other nuclear abnormalities and DNA single-strand breaks evaluated by single cell gel electrophoresis assay on circulating blood cells were employed as endpoints for genotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 93 publications
0
9
0
3
Order By: Relevance
“…The conducted studies mainly focused on the evaluation of environmental stressors such as agrochemicals and heavy metals in vivo. [223,[227][228][229][230][231][232][233][234][235][236][237], fungicides (captan) [238], pesticides [239,240], antiparasitic agents [239], persistent organic pollutants (POPs) [219] as well as other agrochemicals [241] and poultry litter [242]. These studies indicated the DNA damaging effects of selected chemicals as well as using amphibians as sentinel organisms for the evaluation of environmental pollution.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The conducted studies mainly focused on the evaluation of environmental stressors such as agrochemicals and heavy metals in vivo. [223,[227][228][229][230][231][232][233][234][235][236][237], fungicides (captan) [238], pesticides [239,240], antiparasitic agents [239], persistent organic pollutants (POPs) [219] as well as other agrochemicals [241] and poultry litter [242]. These studies indicated the DNA damaging effects of selected chemicals as well as using amphibians as sentinel organisms for the evaluation of environmental pollution.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, environmental alterations that promote morphological and physiological changes at the tissue level are poorly understood. The liver plays a key role in the detoxification of xenobiotics (Pérez-Iglesias et al, 2018;Fanali et al, 2018), as well as other functions related to the metabolism (Hinton, Segner & Braunbeck, 2001;Fenoglio et al, 2005). The detoxification is performed by hepatocytes and melanomacrophages (MMs) and may be either enzymatic or not.…”
Section: Introductionmentioning
confidence: 99%
“…However, environmental alterations that promote morphological and physiological changes at the tissue level are poorly understood. The liver plays a key role in the detoxification of xenobiotics (Pérez-Iglesias, et al, 2018;Fanali et al, 2018), as well as other functions related to the metabolism (Hinton et al, 2001;Fenoglio et al, 2005). The detoxification is performed by hepatocytes and melanomacrophages and may be either enzymatic or not.…”
Section: Introductionmentioning
confidence: 99%